Bench valvular surgery in donor's hearts before transplantation: Choice versus necessity. Issue 7 (19th April 2022) - El‐Sayed Ahmed, Magdy M.; Pham, Anthony; Sareyyupoglu, Basar; Pham, Si M.
Abstract: The severe shortage of donor's hearts has increased the mortality of patients on the transplant waiting list. However, donor hearts with valvular dysfunction are rarely used. Utilizing donor hearts with valvular lesions that can be repaired or replaced at the time of transplant will decrease waitlist mortality and offer many patients a second chance in life.